A licenciatura em matemática: um estudo comparativo entre a modalidade presencial e a distância - Bandeira Junior, Chateaubriand Pinto (2009)
Considering the phenomenon of New Information and Communication Technologies (ICTs), faced by contemporary society, especially within education, it is highlighted the necessity of the practice of a comparative study of perceptions of teachers about the presence and distance courses: the case of education degree in mathematics from the UAB / UFPB. Furthermore, based on a literature search, which was derived ideas of renowned authors who focus on the topic in question, this dissertation aimed to investigate the perceptions of seven professors of education about presence and distance education, the courses of UAB / UFPB and the differences between these two forms of education. For data collection was used as an instrument, an interview with open questions, and done in an individual way , in the environment where teachers work in the presence and distance courses in order to examine the testimony of those on various questions that point for the possible differences that may exist in these courses. The type of search used by the researcher was the qualitative research, which is concerned with a level of reality that can not be quantified and to work with the universe of meanings that can not be restricted to the operationalization of variables. Thus, it was structured as follows: an introduction, over 6 chapters: theoretical framework, education and the teaching of mathematics: challenges and the teaching of mathematics in EAD; education mediated by computer; methodological route; data discussion; followed from the final considerations, references and the Appendix.